Nutrition Knowledge and Dietary Habits of Patients with Type-2 Diabetes Attending the Regional Hospital at Wa - Issah, R. (University of Ghana, 2016)
Background: Chronic diseases such as type-2 diabetes require continuous medical care and ongoing patient self-management education and support to prevent multiple complications and premature mortality. Adequate nutrition knowledge and appropriate dietary habits play key roles in the nutritional management of type-2 diabetes. Therefore, providing adequate nutrition information and skills on indicators such as good diet, physical activity, and health have been shown to improve the well-being of the individual and/or groups. Aim: To assess the nutrition knowledge and dietary habits of patients with type-2 diabetes attending the Regional hospital at Wa in the Upper West Region of Ghana. Method: A cross-sectional study was conducted to assess the nutrition knowledge and dietary habits of patients with type-2 diabetes using systematic random sampling technique. One hundred and seventeen (117) participants were involved in the study. Key indicators investigated in the study were nutrition knowledge, dietary habits, body fat composition, percentage visceral fat, body mass index and glycated haemoglobin levels. The relationship between dietary habits and body fat composition; percentage visceral fat; body mass index; glycated haemoglobin levels were also investigated. The raw data solicited from the study participants were entered into excel and transferred into statistical package for social sciences (SPSS) version 20 software for analyses. Using chi-square and correlation analysis, associations between the variables of interest were established with a level of significance (p<0.05). The results of the analyses were presented as standard deviations, numbers and percentages using tables and graphs. The nutrition knowledge of the study participants was scored using a standard scale of reference. Results: Key findings of the study showed below average nutrition knowledge (45.3%) and dietary habits generally indicated a poor nutritional status among the study participants. The mean BMI for the female and male participants were 28.59±4.699kgm-2 and 24.96±4.019kgm-2 respectively. There was a significant association between dietary habits and body fat composition; percentage visceral fat; BMI level and glycated haemoglobin level (p< 0.05). Conclusion: It was concluded that below average nutrition knowledge was associated with poor dietary habits and nutritional status. Type-2 diabetic subjects should therefore be encouraged to take part in nutrition education programmes in order to effectively manage the disease.
Thesis(MSc)-University of Ghana, 2016
Keywords: Nutrition Knowledge; Dietary Habits; Type-2 Diabetes; Wa